Parental reports on the lexicon of children from diverse bilingual populations - Ohana, Odelya; Armon-Lotem, Sharon (Frontiers in Psychology, 2023)
Parental questionnaires have been widely used to assess children's vocabularies. The MacArthur-Bates Communicative Developmental Inventories (MB-CDI) have been adapted into over 100 languages, providing researchers with access to various languages. As the vocabularies of bilingual children are distributed across their two languages, language knowledge must be assessed in both languages. While this can be done with two questionnaires, one for each language, the present study makes use of a multicultural adaptation of the MB-CDI, within a single questionnaire, that was geared specifically for bilingual context. In order to explore the developmental trajectories of the vocabularies of 90 bilingual children from diverse linguistic populations (English-Hebrew (n=30), French-Hebrew (n=30), and Russian-Hebrew (n=30) speaking families) parents reported on both the Home Language (HL) and the Societal Language-Hebrew (SL-Hebrew). Parents also provided background information about the child, the child's family, and exposure to each language. Our findings show no significant difference between vocabulary size of children from diverse bilingual populations in the HL and the SL, for both production and comprehension. Moreover, children from all three groups demonstrate balanced bilingualism at the group level. Correlations were found between both exposure to and use of each language by children, and various vocabulary measures across the three groups. The similar vocabulary levels demonstrated by the three groups as well as the balanced bilingualism can be explained by the relatively high prestige of all languages tested. Exposure to each language shows support in that language and a negative effect on the other language, demonstrating the crucial role exposure plays in bilingual children's language performance.